Gas Exchange Relations of Ungrafted Grapevines (cv. Carménère) Growing Under Irrigated Field Conditions - Jara-Rojas, F.; Ortega-Farías, S.; Valdés-Gómez, H.; Acevedo-Opazo, C. (South African Journal of Enology and Viticulture, 2016)
A study was carried out to evaluate the leaf gas exchange relations and water-use efficiency (WUE) of ungrafted Carménère (Vitis vinifera L.) grapevines growing under field conditions and different levels of water stress. Stomatal conductance (gs), transpiration (E), net CO2 assimilation (AN) and stem water potential (Ψs) were measured at midday in a drip-irrigated commercial vineyard located in the Maule Valley (Chile) during three growing seasons (2005 to 2009). In addition, the instantaneous (AN/E) and intrinsic (AN/gs) water-use efficiencies and stomatal sensitivity factor (k) were estimated for the own-rooted grapevines. In this study a significant non-linear relationship was observed between AN and gs (r2 = 0.82), with values of AN decreasing from 14.9 to 3.5 μmol/m2/sec as gs diminished from 0.5 to 0.05 mol/m2/sec. This resulted in a progressive increase in WUEi (intrinsic water use efficiency). A significant linear relationship was observed between Ψs and gs (r2 = 0.39) for measurements taken before and after véraison, with an increasing scattering from -1.6 to -0.4 MPa. Finally, k decreased as water stress increased, with values of 234 and 120 for no and severe water stress respectively, while k ranged from 264 to 480 and 255 to 297 for the measurements taken before and after véraison respectively. Based on the results obtained in the present study, the cultivar Carménère could be classified as drought tolerant at low water potentials, with a large range of physiological parameters changing in response to water stress.